2009
DOI: 10.1111/j.1460-2695.2009.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Sickle‐shaped surface crack in a notched round bar under cyclic tension and bending

Abstract: A B S T R A C T A sickle-shaped surface crack, also called crescent-moon (or crescent) crack, is assumed to exist at the root of a circular-arc circumferential notch in a round bar under tension and bending. For different notch sizes (i.e. different values of the stress concentration factor), the stress intensity factor along the crack front is computed through a three-dimensional finite-element analysis. The effect of the stress concentration factor on the stress intensity factor values is examined for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…The problem of such vertex singularities, also called corner point singularities, is well documented in a number of papers covering the last 30 years (see, among others, Bažant and Estenssoro, 11 Pook, 12–14 She and Guo, 15 Yu et al 16 ). The same problem has recently been analysed for fatigue strength problems by Carpinteri et al, 17,18 Doquet et al 19 and Hutar et al 20 Hutar considered the effect of free surfaces on fatigue crack behaviour for relatively thick specimens, where the solutions by Benthem and Bažant for a semi‐infinite body remains valid. Later, dealing with thin structures, a detailed numerical investigation demonstrated that the effect of 3D stress distributions on crack behaviour remains an open problem of major interest in Fracture Mechanics 20 …”
Section: Introductionmentioning
confidence: 99%
“…The problem of such vertex singularities, also called corner point singularities, is well documented in a number of papers covering the last 30 years (see, among others, Bažant and Estenssoro, 11 Pook, 12–14 She and Guo, 15 Yu et al 16 ). The same problem has recently been analysed for fatigue strength problems by Carpinteri et al, 17,18 Doquet et al 19 and Hutar et al 20 Hutar considered the effect of free surfaces on fatigue crack behaviour for relatively thick specimens, where the solutions by Benthem and Bažant for a semi‐infinite body remains valid. Later, dealing with thin structures, a detailed numerical investigation demonstrated that the effect of 3D stress distributions on crack behaviour remains an open problem of major interest in Fracture Mechanics 20 …”
Section: Introductionmentioning
confidence: 99%
“…As far as surface cracks emanating from notches in particular structural components are concerned, Erjian 112 determined the SIF in the case of circumferential cracks in notched round bars by using approximate analyses; Lin and Smith 113 and Carpinteri et al [114][115][116][117][118] used the finite element (FE) analyses to determine the mode I SIF for various notched structural components such as plates, 113 circumferentially notched round bars, [114][115][116] notched pipes and shells. 117,118 Other complex structural components containing stress raisers, such as welded joints, round bars and railway axels, were examined by Carpinteri et al, 119 Fonseca et al 120 and Madia et al 121 (in the last paper mentioned, a wide collection of SIF solutions is reported for various crack sites in T-notched and V-notched components).…”
Section: Cracks In Notched Structural Componentsmentioning
confidence: 99%
“…Therefore, during the last two decades, the present authors have extensively examined the following cracked notched solids: double‐curvature shells (i.e. shells with two distinct principal curvature radii), such as pressure vessels, pipe elbows and fuel tanks; and round bars, such as bolts, screws, pins, reinforcements, tendons for prestressed concrete structures and supports in suspension and stayed bridges …”
Section: Introductionmentioning
confidence: 99%
“…By employing the aforementioned SIF results, the fatigue behaviour is examined. In particular, crack paths, crack growth rate curves and crack front evolutions are determined by employing a theoretical model and compared with some data available in the literature.…”
Section: Introductionmentioning
confidence: 99%